High‐Efficiency Polymer Solar Cells Enhanced by Solvent Treatment. (28th January 2013) - Zhou, Huiqiong; Zhang, Yuan; Seifter, Jason; Collins, Samuel D.; Luo, Chan; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> A significant enhancement of efficiency in thieno[3, 4‐b]‐thiophene/benzodithiophene:[6, 6]‐phenyl C71‐butyric acid methyl ester (PTB7:PC70BM) solar cells can be achieved by methanol treatment. The effects of methanol treatment are shown in an improvement of built‐in voltage, a decrease in series resistance, an enhanced charge‐transport property, an accelerated and enlarged charge extraction, and a reduced charge recombination, which induce a simultaneous enhancement in open‐circuit voltage (Voc), short‐circuit current (Jsc), and fill factor (FF) in the devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>